Transnasal Endoscopy Removal of Dislodged Dental Implant: A Case Report - Lim, D.; Parumo, R.; Ma, B.C.; Shanmuganathan, J. (American Academy of Implant Dentistry, 2017)
Displacement of dental implants into the maxillary sinus is a rare complication. This article presents a case of displaced dental implant into maxillary sinus. Retrieval of the dental implant from left maxillary sinus was performed via endoscopic sinus surgery. This case highlighted a delayed referral of a 53-year-old male by a general dental practitioner for management of a dislodged dental implant into the left maxillary antrum. The implant was dislodged during placement of a healing abutment 4 months after implant insertion to replace missing 25. Cone beam computerized tomography revealed the displaced implant was located at the ostium of the left nose. A sudden change in sinonasal pressure when the patient took a deep breath during the procedure may have created a negative pressure and suction effect causing the implant to be dislodged and embedded at the ostium. In view of its position, a referral to an otorhinolaryngologist was made for endoscopic removal of the displaced implant. This case also highlighted the need for inter disciplinary cooperation in the management of such a complication for the best interest of the patients.